B Cell Siglecs–News on Signaling and Its Interplay With Ligand Binding - Sarah J. Meyer; Alexandra T. Linder; Carolin Brandl; Lars Nitschke (Frontiers in Immunology, 2018)
CD22 and Siglec-G are members of the Siglec family. Both are inhibitory co-receptors on the surface of B cells and inhibit B-cell receptor induced signaling, characterized by inhibition of the calcium mobilization and cellular activation. CD22 functions predominantly as an inhibitor on conventional B cells, while Siglec-G is an important inhibitor on the B1a-cell subset. These two B-cell Siglecs do not only inhibit initial signaling, but also have an important function in preventing autoimmunity, as double deficient mice develop a lupus-like phenotype with age. Siglecs are characterized by their conserved ability to bind terminal sialic acid of glycans on the cell surface, which is important to regulate the inhibitory role of Siglecs. While CD22 binds α2,6-linked sialic acids, Siglec-G can bind both α2,6-linked and α2,3-linked sialic acids. Interestingly, ligand binding is differentially regulating the ability of CD22 and Siglec-G to control B-cell activation. Within the last years, quite a few studies focused on the different functions of B-cell Siglecs and the interplay of ligand binding and signal inhibition. This review summarizes the role of CD22 and Siglec-G in regulating B-cell receptor signaling, membrane distribution with the importance of ligand binding, preventing autoimmunity and the role of CD22 beyond the naïve B-cell stage. Additionally, this review article features the long time discussed interaction between CD45 and CD22 with highlighting recent data, as well as the interplay between CD22 and Galectin-9 and its influence on B-cell receptor signaling. Moreover, therapeutical approaches targeting human CD22 will be elucidated.